Analysis Of The Impact Of Tax Burden, Profitability, Sales Growth, And Company Size On Transfer Pricing : Case Study On Manufacturing Companies In The Consumer Goods Industry Sector Listed On The Indonesia Stock Exchange For The Period 2021-2023) - Tartila, Nilda; Putri, Wulan Wahyuni Rossa (Institut Bisnis dan Informatika Kesatuan, 2024)
The aim of this research is to determine the effect of tax burden, profitability, sales growth and company size on transfer pricing. The nature of this research is quantitative. The research sample used purposive sampling and obtained 30 companies is food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange in 2021-2023. This research uses secondary data in the form of financial reports and company annual financial reports downloaded from www.idx.co.id and the websites of each company sampled in this research. Data analysis uses multiple linear analysis. The results of this research show that tax burden and profitability influence transfer pricing. Meanwhile, sales growth and company size have no effect on transfer pricing. Also, tax burden, profitability, sales growth and company size simultaneously influence transfer pricing. Keywords : tax burden, profitability, sales growth, company size, transfer pricing